2006
DOI: 10.1097/01.md.0000236952.87590.c8
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Restoration of Pulmonary Perfusion in a Long-Term Follow-Up of Patients After Acute Pulmonary Embolism

Abstract: We followed prospectively 834 consecutive patients (70% inpatients), evaluated for suspected pulmonary embolism, for a median time of 2.1 years (range, 0-4.8 yr), and compared the survival rates in patients with proven pulmonary embolism (n=320) with those without (n=514). In multivariate analysis, we modeled the probability of surviving in patients with pulmonary embolism as a function of the extent of pulmonary vascular obstruction at baseline. Among patients with pulmonary embolism, a scintigraphic follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
149
2
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(168 citation statements)
references
References 24 publications
10
149
2
7
Order By: Relevance
“…[3][4][5] Resolution occurs by mechanical fragmentation, 6 through organization of the thromboembolus by invasion of endothelial cells (ECs), mononuclear cells, and fibroblasts leading to recanalization, and through endogenous thrombolysis. In 0.1%-9.1% [7][8][9][10][11][12][13][14][15][16] of cases, venous thromboemboli fail to resorb, thereby resulting in CTEPH or in permanent occlusion of the deep veins.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Resolution occurs by mechanical fragmentation, 6 through organization of the thromboembolus by invasion of endothelial cells (ECs), mononuclear cells, and fibroblasts leading to recanalization, and through endogenous thrombolysis. In 0.1%-9.1% [7][8][9][10][11][12][13][14][15][16] of cases, venous thromboemboli fail to resorb, thereby resulting in CTEPH or in permanent occlusion of the deep veins.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although the incidence of CTEPH is usually estimated to be <1% among patients with acute PE, [2][3][4] several studies have proposed that this low incidence was an underestimation and showed approximately 4%, a relatively high incidence of CTEPH after PE. [5][6][7] In addition, it has not been shown why some PE patients develop CTEPH and others do not.…”
Section: Introductionmentioning
confidence: 99%
“…In Table 6 Radiographic findings in 397 subjects with and without COPD. our experience, perfusion lung scintigraphy should also be obtained for it allows detecting multiple segmental or lobar perfusion defects that are the hallmark of chronic thromboembolic pulmonary hypertension [24]. This is amenable of surgical repair if the organized clots are located in the proximal branches of the pulmonary circulation [1,2,8,10].…”
Section: Discussionmentioning
confidence: 99%